2022
DOI: 10.1002/asia.202200485
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Practical Synthesis of C1 Deuterated Aromatic Aldehydes Enabled by Catalysis and Beyond

Abstract: C 1 -selective deuteration of aromatic aldehydes is of great importance for isotopic labeling and for improving the characteristics of drug molecules. Due to the recent increase in the use of deuterated pharmacological drugs, there is a pressing need for synthetic procedures that are efficient to produce deuterated aromatic aldehyde analouges. Deuterium labeling approaches are typically used as an effective tool for researching pharmaceutical absorption, distribution, metabolism, and excretion (ADME). Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Since then, numerous research groups have reported variations of the pyrrolidine‐based triazolium salt and their significant synthetic applications (Figure 1). [32–49] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, numerous research groups have reported variations of the pyrrolidine‐based triazolium salt and their significant synthetic applications (Figure 1). [32–49] …”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous research groups have reported variations of the pyrrolidine-based triazolium salt and their significant synthetic applications (Figure 1). [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] The benzoin coupling reaction has been widely investigated in the field of NHC-mediated organocatalysis. Using cyanide (NaCN, KCN) as a readily available, inexpensive catalyst, Wöhler and Liebig first identified this reaction in 1832.…”
Section: Introductionmentioning
confidence: 99%